2012
DOI: 10.1007/s13149-012-0246-9
|View full text |Cite
|
Sign up to set email alerts
|

Profil clinicobiologique, thérapeutique et évolutif des patients infectés par le VIH hospitalisés au service des maladies infectieuses et tropicales d’Abidjan (Côte d’Ivoire)

Abstract: The objective of this study is to describe the clinical, biological, therapeutic and evolving current profile of hospitalized patients with HIV infection in the cohort of the Infectious and Tropical Diseases Unit (ITDU) in the aim to improve their care management. This is a retrospective study, conducted on medical data of hospitalized cases of patients with HIV infection in the ITDU at the teaching hospital of Treichville (Abidjan) from 2006 to 2007. During the two years, 447 patients were included in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
5
0
2
Order By: Relevance
“…Ceci est en conformité avec les résultats de Kouanfack et al qui avaient retrouvé au Cameroun un délai médian de 2,3 mois (18). Par contre, Kra et al avaient trouvé un délai de 5 mois (19). Ce délai dans cette étude est réduit, car les patients se trouvaient déjà à un stade avancé de la maladie au moment de l'initiation du TARV.…”
Section: Discussionunclassified
“…Ceci est en conformité avec les résultats de Kouanfack et al qui avaient retrouvé au Cameroun un délai médian de 2,3 mois (18). Par contre, Kra et al avaient trouvé un délai de 5 mois (19). Ce délai dans cette étude est réduit, car les patients se trouvaient déjà à un stade avancé de la maladie au moment de l'initiation du TARV.…”
Section: Discussionunclassified
“…Available data come mainly from research protocols, clinical trials or specifically designed cohort studies, which may differ from routine programs by the selection of the population and by the means engaged to diagnose clinical events. Moreover, most available data concerning hospitalizations come from retrospective studies [1822]. …”
Section: Introductionmentioning
confidence: 99%
“…Zannou [6] and Kra [7] had also made the same remark. Whereas Shen et al [8] reported a male predominance.…”
Section: Discussionmentioning
confidence: 63%
“…According to Kra [7] the reasons of hospitalisation were dominated by tuberculosis (34.2%), cerebral toxoplasmosis (17.9%) and neuromeningeal cryptococcosis (8%).…”
Section: Cd4 Cells Levelmentioning
confidence: 99%